THE FUNCTIONAL RECOVERY OF THE UPPER LIMB IN CHILDREN WITH CEREBRAL PARALYSIS - Haidamac Ana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The precocity of proper diagnostics, establishment of a supported therapy program, 2-3 times per day, for 25 to 30 minutes , lot of patience, understanding, and professionalism will lead to the reduction of spasticity, learning to actively relax in correct and comfortable positions, formation of correct motion engrams, increase joint mobility parameters, stretching slowly, learning and training manual gestures and gripping. Equally important is individualization of therapy, choosing the most appropriate relaxing methods for each child, removing as much as possible the emotional stress, focusing on maintaining the state of relaxation during application using the right speed, depending on the particular response of the child.